A educação financeira no ensino fundamental e o desenvolvimento de atividades para o 9º ano - Freitas, Simone de Fatima (2020)
This dissertation deals with the development of activities for Financial Education in a class of 9th grade of elementary School. Its goal objective is to contribute to the citizen formation of each student, in order to improve financial literacy with activities present in daily life. Financial Education is important for autonomy and decision making, affecting directly the economic development of society, thus, it is very important that it starts already in Basic Education. This paper presents a Common National Curriculum Base (CNCB) analysis of the and the contents of financial mathematics/financial education planned for each school year. This work is also part of five activities that can be applied and explored in the teaching of Financial Education. Such activities were applied to the 9th grade B class, from the Horácio Soares state school, in the city of Ourinhos-SP. After application and analyzing of the activities we can see the need to insert Financial Education in teaching practice, in order to provide students with financial literacy, making use of financial mathematics as a tool for decision making. In the reflections provided by this work, we perceive, by the return of the students themselves participating in the applied activities, the need to learn more about topics related to their financial life and thus be better prepared for life.